1998
DOI: 10.1098/rspb.1998.0468
|View full text |Cite
|
Sign up to set email alerts
|

Snail sperm production characteristics vary with sperm competition risk

Abstract: Sperm competition is widespread and in£uences both male investment in spermatogenic tissue and ejaculate characteristics. Sperm competition models assume trade-o¡s between sperm size and number, although such trade-o¡s may be di¤cult to detect. This study examines the e¡ects of sperm competition risk on the sperm production characteristics of the freshwater snail Viviparus ater. In this prosobranch, females mate frequently and store sperm, generating sperm competition. Males produce two sperm morphs, fertile e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 47 publications
(68 reference statements)
5
72
5
Order By: Relevance
“…In addition, although we looked over five copulations, trade-offs may only be detected over a lifetime. A negative association between sperm size and number is a key assumption of sperm competition theory (Pizzari and Parker, 2009), but one for which there is only limited support (for example, see Pitnick, 1996;Oppliger et al, 1998). This is, at least, partly because of the difficulties in assessing the predicted negative association (Pitnick, 1996;Pizzari and Parker, 2009), but in any case, we find no evidence indicative of a trade-off-with the caveats given above, which make the test rather weak.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, although we looked over five copulations, trade-offs may only be detected over a lifetime. A negative association between sperm size and number is a key assumption of sperm competition theory (Pizzari and Parker, 2009), but one for which there is only limited support (for example, see Pitnick, 1996;Oppliger et al, 1998). This is, at least, partly because of the difficulties in assessing the predicted negative association (Pitnick, 1996;Pizzari and Parker, 2009), but in any case, we find no evidence indicative of a trade-off-with the caveats given above, which make the test rather weak.…”
Section: Discussioncontrasting
confidence: 56%
“…This is carried out to manipulate male perception of the immediate SCI in the subsequent test copulation. Such an experimental design is encountered frequently (Gage & Barnard, 1996;Oppliger et al, 1998;Evans & Magurran, 1999b;Schaus & Sakaluk, 2001;Candolin & Reynolds, 2002;Evans et al, 2003;Pizzarri et al, 2003). However, manipulating male perception of immediate SC in this way possibly also affects male perception of mean SC.…”
Section: Pitfall 1: Testing Mean and Immediate Responsesmentioning
confidence: 99%
“…Oppliger et al, 1998;Evans & Magurran, 1999b;Evans et al, 2003;Reinhardt & Arlt, 2003). With sex ratio manipulation we do not mean the manipulation of immediate SCI by, e.g.…”
Section: Pitfall 4: the Possible Consequences Of Sex Ratio Manipulationmentioning
confidence: 99%
“…It has previously been shown for several species that sperm characteristics, such as sperm density, milt volume or flagellum length, vary according to different mating tactics of males (Leach & Montgomerie, 2000;Neff et al, S P E R M C H A R A C T E R I S T I C S I N P E R C H 2003; Aspbury & Gabor, 2004) or according to the expected sperm competition intensity (Oppliger et al, 1998;Uglem et al, 2002). In Atlantic salmon Salmo salar L., for example, no difference in flagellum length could been found between parr and anadromous males (Vladic et al, 2002), but parr males showed higher sperm density, higher investment in gonads and more motile sperm 10 s after initiation than anadromous males (Vladic & Ja¨rvi, 2001).…”
Section: S P E R M C H a R A C T E R I S T I C S I N P E R C H 1897mentioning
confidence: 99%